Pengaruh Teknologi Informasi dan Digital Payment terhadap Kinerja Keuangan dengan Literasi Digital sebagai Variabel Moderasi (Survei pada Sub Sektor Kerajinan Tangan di Night Market Ngarsopuro Surakarta) - Apriliani Saputri; Dewi Saptantinah (ProBank, 2025)
This study aims to analyze the effect of information technology and digital payments on financial performance, as well as to examine the role of digital literacy as a moderating variable in the creative economy sector, particularly in the handicraft sub-sector at the Ngarsopuro Night Market in Surakarta. Using quantitative methods through a survey of 52 MSME actors, the results show that both information technology and digital payments have a positive and significant effect on financial performance. However, another important finding is that digital literacy has not been able to moderate or strengthen this relationship. This indicates that although the use of technology and digital payments has a positive impact, the limited level of digital understanding and expertise among MSME players remains a challenge that needs to be overcome in order to optimize the full potential of digitalization. The results of this study are expected to provide input for MSMEs to improve their digital capacity, as well as serve as a basis for consideration by the government and related parties in formulating more effective policies to improve digital literacy.